2023
DOI: 10.1590/1983-1447.2023.20230077.en
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with loss to follow-up in tuberculosis treatment in Brazil: a retrospective cohort study

Lucas Vinícius de Lima,
Gabriel Pavinati,
Isadora Gabriella Silva Palmieri
et al.

Abstract: Objective: To analyze the factors associated with loss to follow-up in tuberculosis cases among adults in Brazil in 2020 and 2021. Method: Retrospective cohort with secondary data from the Brazilian Notifiable Diseases Information System. A total of 24,344 people diagnosed with tuberculosis whose information was complete in the database were included. Adjusted odds ratios and confidence intervals were estimated by binary logistic regression. Results: Higher odds of loss to follow-up were observed for males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(20) In the Brazilian context, a retrospective cohort study identified factors leading to loss of follow-up for tuberculosis treatment when compared with the cure outcome. (21) Among the vulnerabilities, the following stood out: male gender (adjusted OR [aOR] = 1.35; 95% CI: 1.23-1.46); non-white ethnicity/race (aOR = 1.16; 95% CI: 1.07-1.26); drug use (aOR = 1.84; 95% CI: 1.66-2.04); and entry as recurrence (aOR = 1.33; 95% CI: 1.15-1.53) or re-entry after abandonment (aOR = 4.31; 95% CI: 3.90-4.77). (21) To achieve the goals of reducing new cases and deaths from the disease by 2030, it is necessary and urgent to advance and overcome existing care gaps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(20) In the Brazilian context, a retrospective cohort study identified factors leading to loss of follow-up for tuberculosis treatment when compared with the cure outcome. (21) Among the vulnerabilities, the following stood out: male gender (adjusted OR [aOR] = 1.35; 95% CI: 1.23-1.46); non-white ethnicity/race (aOR = 1.16; 95% CI: 1.07-1.26); drug use (aOR = 1.84; 95% CI: 1.66-2.04); and entry as recurrence (aOR = 1.33; 95% CI: 1.15-1.53) or re-entry after abandonment (aOR = 4.31; 95% CI: 3.90-4.77). (21) To achieve the goals of reducing new cases and deaths from the disease by 2030, it is necessary and urgent to advance and overcome existing care gaps.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Among the vulnerabilities, the following stood out: male gender (adjusted OR [aOR] = 1.35; 95% CI: 1.23-1.46); non-white ethnicity/race (aOR = 1.16; 95% CI: 1.07-1.26); drug use (aOR = 1.84; 95% CI: 1.66-2.04); and entry as recurrence (aOR = 1.33; 95% CI: 1.15-1.53) or re-entry after abandonment (aOR = 4.31; 95% CI: 3.90-4.77). (21) To achieve the goals of reducing new cases and deaths from the disease by 2030, it is necessary and urgent to advance and overcome existing care gaps. To this end, we suggest expanding diagnostic testing, timely and adequate reporting of new cases, guaranteeing general access to health care for treatment follow-up, mitigation of disease risk factors (focusing on countries with the highest burden and among vulnerable populations), and expanding investments in research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show a significant rate of recurrence attributed to males and individuals aged over 15 years old. Notably, men are more likely to engage in behaviors, such as difficulties in identifying their health demands and the non-adoption of protective practices, that can lead to unfavorable treatment outcomes (e.g., loss to follow-up) 4,19,20 . This could explain the higher proportion of TB recurrence in this group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, the TB incidence rate in Brazil was 37.4 cases per 100,000 inhabitants, with a mortality rate of 2.61 deaths per 100,000 inhabitants 2 . The country faces numerous challenges in controlling the disease, such as healthcare resource inequalities, low education levels, income and occupation disparities, high population density in vulnerable socioeconomic territories, poor living conditions, and elevated loss to follow-up rates that sustain the transmission chain 3,4 .…”
Section: Introductionmentioning
confidence: 99%